Social impact on the generation of employment and access to goods and services of associative models in the municipality of Espinal, Tolima - Rodríguez Vargas, Derly Milena (Cooperativismo & Desarrollo, 2022)
The solidarity economy refers to a different method of doing economy, based on the participation of society, in the construction of present and future quality of life that generate guarantees for the general welfare, solidarity and non-profit. To give way to the implementation of the solidarity economy, solidarity organizations are born with the main purpose of promoting social and collective development, but this statement is actually fulfilled? This is how this research seeks to determine the social performance of the savings and credit cooperatives (access to goods and services), and associated work cooperatives (job creation). The research presents a qualitative approach, with a descriptive scope and an inductive study method, through the collection of information with primary and secondary sources. As a result, there is the relevant contribution made by these non-profit entities of the solidarity economy sector to the fulfillment of the Sustainable Development Goals from the fulfillment of their corporate purpose.